2013
DOI: 10.1097/cji.0b013e3182993eb9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20-Interferon-β Fusion Protein Therapy of Murine B-Cell Lymphomas

Abstract: Type I interferons (IFNα/β) are cytokines with a broad spectrum of anti-tumor activities including anti-proliferative, pro-apoptotic, and immunostimulatory effects, and are potentially useful in the treatment of B cell malignancies and other cancers. To improve anti-tumor potency and diminish the systemic side effects of IFN, we recently developed anti-CD20-IFNα fusion proteins with in vitro and in vivo efficacy against both mouse and human lymphomas expressing CD20. Since IFNβ binds more tightly to the IFNα/β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…21,34 Apart from its immunostimulatory effects, IL-21 exerts direct cytotoxicity on a variety of IL-21R-expressing NHLs, including diffuse large B-cell lymphoma (DLBCL), MCL, chronic lymphocytic leukemia, and follicular lymphoma. 32,[35][36][37][38][39][40][41][42] We found that the direct apoptotic effects of IL-21 in DLBCL and MCL were mediated via activation of an IL-21R-dependent signaling pathway that leads to phosphorylation of STATs followed by upregulation of cMyc and Bax and downregulation of BCL-2 and BCL-XL. 32,35 These studies suggest IL-21 may become a potent adjuvant to cancer immunotherapy against B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…21,34 Apart from its immunostimulatory effects, IL-21 exerts direct cytotoxicity on a variety of IL-21R-expressing NHLs, including diffuse large B-cell lymphoma (DLBCL), MCL, chronic lymphocytic leukemia, and follicular lymphoma. 32,[35][36][37][38][39][40][41][42] We found that the direct apoptotic effects of IL-21 in DLBCL and MCL were mediated via activation of an IL-21R-dependent signaling pathway that leads to phosphorylation of STATs followed by upregulation of cMyc and Bax and downregulation of BCL-2 and BCL-XL. 32,35 These studies suggest IL-21 may become a potent adjuvant to cancer immunotherapy against B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 88%
“…In preclinical studies, fusion of type I interferons (IFNa/b) with CD20 mAb demonstrated potent antilymphoma effects in B-cell lymphoma tumor models. 39,40 Fusion of granulocyte-macrophage colony-stimulating factor and IL-21 (GIFT-21) activated immune response and led to antitumor responses in the B16 xenograft model. 41 A recent study of IL-2 fusion with fragment constant (Fc) region (Fc/IL-2) resulted in significant tumor control in isogenic tumor models.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Previous studies in our laboratory [8][9][10][11] have shown that genetic fusion of IFNs to an antibody is an effective strategy to specifically target IFN to the tumor microenvironment, reduce systemic toxicity, and increase half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Our strategy of fusing IFN to antibody has several major advantages in vivo. While the half-life of IFNa is only 1 h, 26 we have shown that fusing it to IgG extends the half-life to 8 h. 10,11 In addition, the anti-CD138 portion of the fusion protein provides a binding specificity to target MM and deliver therapeutically useful levels of IFN without systemic toxicity. Indeed, we have shown the effectiveness of this strategy in targeting not only MM, 8 but also lymphoma using anti-CD20-IFNa2.…”
Section: Combination Of Anti-cd138-ifna14 and Bortezomib Provides Enhmentioning
confidence: 99%
See 1 more Smart Citation